Model for Joint Operation of Multi-Energy Systems in Energy and Frequency Regulation Ancillary Service Markets Considering Uncertainty - Wenqi Hao; Yuxing Liu; Tao Wang; Mingmin Zhang (Energies)
A new type of power system with a high proportion of renewable energy sources (RES) penetration has become a global development trend. Meanwhile, the marketization reforms of the electricity market pose challenges to traditional energy. A multi-energy model including a wind turbine (WT), photovoltaic (PV) energy, energy storage (ES), and a thermal power system is proposed in this paper, participating in a joint market mechanism for energy and frequency regulation ancillary services. Unlike existing joint markets, this paper considers the market coupling clearing of various energy sources and the uncertainty of RES generation. Specially, a mechanism for the participation of storage and thermal power units in the frequency regulation ancillary service market is designed. Finally, a practical 118-node case study is provided to validate the impact of renewable generation uncertainty on the participation of multi-energy coupled systems in joint and single energy markets. Compared to the single electricity energy market, the simulation results show that the model can reduce the impact of RES uncertainty on ES generation and increase the cleared electricity quantity of thermal power units by 16%. Moreover, the model also increases the market revenue of thermal power units and storage by 30% and 44%, respectively.